2008
DOI: 10.1002/lsm.20720
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy as treatment of chronic idiopathic central serous chorioretinopathy

Abstract: Our data suggest that PDT leads to resolution of serous detachments and visual improvement in patients with chronic ICSC. Further follow-up would be prudent to assess the long-term outcomes and safety in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…In Chan et al's study, one juxtafoveal CNV developed 3 months post standard PDT treatment. 23,25,26,30,33,34,36,37,41,46 Variation in verterporfin dose: The variation in verteporin dose PDT group had the best results in terms of resolution of SRF and improvement of BCVA post PDT treatment. In the half-dose verterporfin group, complete resolution of SRF was seen in three out of seven studies (42.9%) at the end of each study's follow-up period.…”
Section: Variation In Treatment Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…In Chan et al's study, one juxtafoveal CNV developed 3 months post standard PDT treatment. 23,25,26,30,33,34,36,37,41,46 Variation in verterporfin dose: The variation in verteporin dose PDT group had the best results in terms of resolution of SRF and improvement of BCVA post PDT treatment. In the half-dose verterporfin group, complete resolution of SRF was seen in three out of seven studies (42.9%) at the end of each study's follow-up period.…”
Section: Variation In Treatment Parametersmentioning
confidence: 98%
“…Mean laser spot size ranged between 1300 and 6800mm. 15,[17][18][19][20][21][22][23][24][25][26][27][29][30][31][33][34][35][36][37]39,[41][42][43][44]46,47 Thirteen studies (n ¼ 13, 54.2%) used a mean spot size o4500 mm. The spot size was not mentioned in seven studies.…”
Section: Variation In Treatment Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown favorable results with PDT in treating chronic CSC [4][5][6][7][8][9][10][11][12][13][14][15][16]. Our report is the first one to describe the efficacy, the safety, and the chorioretinal changes 5 or more years after standard PDT for chronic CSC.…”
Section: Discussionmentioning
confidence: 62%
“…The high rate of spontaneous resolution provides that conservative management can be adopted as first-line treatment in most cases [3]. Photodynamic therapy (PDT) with verteporfin has shown good results, both anatomic and functional, in treating chronic CSC, with either standard or reduced fluence (600 mW/cm 2 , 300 mW/cm 2 respectively) and with either standard or half dose (6 mg/m 2 or 3 mg/m 2 respectively) [4][5][6][7][8][9][10][11][12][13][14][15][16]. However, it has been reported that PDT can be associated with potential side-effects, such as RPE atrophy, neuroretinal thickness (NRT) thinning, development of choroidal neovascularization (CNV), and reduction in macular function [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%